2017
DOI: 10.1093/intqhc/mzx132
|View full text |Cite
|
Sign up to set email alerts
|

Are data from national quality registries used in quality improvement at Swedish hospital clinics?

Abstract: While there were significant differences between registries in key factors such as management interest, use of NQR data in local quality improvement seems rather prevalent, at least for Riksstroke. The link between the registry's level of development and factors important for routinization of innovations such as NQRs needs investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…This study showed that the type of registry and its potential use may be connected to what kind of data is registered, the specific condition or type of care process followed, whether it is acute/short or chronic/life-long intervention, and if the registry focuses on diagnosis or on risk assessments and prevention. This has also been observed by Fredriksson et al [ 14 ] studying the usefulness of using data from the NQRs for QI. These observations should guide further studies on strategies to promote the use of NQRs.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…This study showed that the type of registry and its potential use may be connected to what kind of data is registered, the specific condition or type of care process followed, whether it is acute/short or chronic/life-long intervention, and if the registry focuses on diagnosis or on risk assessments and prevention. This has also been observed by Fredriksson et al [ 14 ] studying the usefulness of using data from the NQRs for QI. These observations should guide further studies on strategies to promote the use of NQRs.…”
Section: Discussionsupporting
confidence: 68%
“…It has since then been followed by an increasing number of registries, today more than 100, focusing on specific disorders or healthcare processes [ 8 ]. Three certification levels were introduced in 2012 to assess the maturity and quality of a registry based on a set of indicators [ 14 ]. The certification process is led by an executive committee appointed by the Swedish Association of Local Authorities and Regions (SALAR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of lung cancer registered in the Swedish National Quality Registry for Lung Cancer (NLCR) is around 3000 patients a year, compared to 13.000 patients newly diagnosed lung cancer patients in the Netherlands. Patient coverage in the NLCR was 94 % in 2014, which is comparable with the DLCA-L [24]. As to our knowledge, outcomes of lung cancer quality indicators from the NLCR are not reported.…”
Section: Comparison With Other Auditsmentioning
confidence: 54%
“…This linkage could also be possible for the DLCA-L, using the questionnaires chosen by the International Consortium for Healthcare Outcomes Measurement (ICHOM) [29]. Individual participating hospitals are already using PROMs in daily clinical care, but these data are not yet linked to the clinical data from the DLCA-L. Other lung cancer registries, such as the Danish and Swedish, have included PROMs to measure the quality of life [3,24].…”
Section: Future Perspectivesmentioning
confidence: 99%